قَضَيَّةُ الخُصُومَةِ بَيْنَ القُدَمَاءِ وَالمُحْدَثِينَ وَتَجَلِّيَاتِهَا فِي النَّقْدِ العَرَبِيِّ القَدِيمِ - طارق, زيناي (جامعة الوادي - University of Eloued, 2021)
لقد تجلت ظاهرة القديم والحديث أو القدامى والمحدثين في النقد العربي القديم كرجع صدى لظهور مستجدات في الساحة الثقافة العربية، لعلَّ أهمها انحراف مسار اللغة والشعر العربي عمَّا كان عليه في الجاهلية وصدر الإسلام، إلا أنَّ السبب الحقيقي في ظهور هذه القضية في الساحة النقدية يرجع إلى الخصومة الكبيرة التي حدثت بين أنصار أبي تمام وأنصار البحتري في القرن الرابع الهجري، ولكن مع هذا يجب الاعتراف بأنَّ هذه قضية - بغض النظر عن أسبابها ودواعيها - قد عرفتها كل آداب الأمم تقريبا، وما زالت تبعاتها حتى وقتنا هذا، وستستمرُّ حتى يرث الله الأرض ومن عليها، ما دام هناك سيرورة زمنية وسنة كونية تجعل من جديد اليوم هو قديم الغد، وهي لا تقتصر على الأدب والشعر فقط، بل هي تمسُّ كل مناحي الحياة المادية والثقافية والفكرية والحضارية، والذي يهمنا من كل هذا هو التعرُّف على أطراف هذه القضية؛ أي أنصار شعر القدامى وأنصار شعر المحدثين والموفِّقين بينهما، والتي تعرف في النقد الأدبي بقضية : الخصومة بين القدماء والمحدثين. The phenomenon of the old, the modern or the old and the modern was manifested in the old Arab criticism as an echo of the emergence of new developments in the Arab culture, perhaps the most important of which is the deviation of the course of Arabic language and poetry from what it was in ignorance and the issue of Islam, but the real reason for the emergence of this issue in the monetary arena is due to the great rivalry that occurred between supporters of Abu Tammam and supporters of al-Bahteri in the fourth century, but with this recognition must be that this issue - regardless of its causes and reasons - has been known by almost all nations, Its consequences continue to this day, and will continue until God inherits the earth and those on it, as long as there is a process of time and a universal year that makes it a new day is the old of tomorrow, and it is not limited to literature and poetry, but it touches all aspects of material, cultural, intellectual and civilizational life, which concerns us all about getting to know the edges of this issue, i.e. the supporters of the poetry of the old and the new and the faithful, which are known in literary criticism as the cause of the cause of the revolution The antagonism between the ancients and the modern.
Issue Of Antagonism Between The Ancients And The Modernists And Its Manifestations In The Old Arab Criticism
Keywords: الخصومة؛ القدماء؛ المحدثون؛ النقد؛ العربي؛ القديم